2016
DOI: 10.1038/srep23966
|View full text |Cite
|
Sign up to set email alerts
|

Clustering mechanism of ethanol-water mixtures investigated with photothermal microfluidic cantilever deflection spectroscopy

Abstract: The infrared-active (IR) vibrational mode of ethanol (EtOH) associated with the asymmetrical stretching of the C-C-O bond in pico-liter volumes of EtOH-water binary mixtures is calorimetrically measured using photothermal microfluidic cantilever deflection spectroscopy (PMCDS). IR absorption by the confined liquid results in wavelength dependent cantilever deflections, thus providing a complementary response to IR absorption revealing a complex dipole moment dependence on mixture concentration. Solvent-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…[3] The preferentialh ydration of ap rotein in the presenceo fc osolvents may be regardeda saresult of the delicate balance of three different contributions:arepulsion and an attraction between the protein andc osolventa nd the steric exclusion of the cosolvents acting as classical" crowders". [7][8][9][10][11][12][13][14][15][16][17][18][19] It has been concluded that the conventional "iceberg" modeli sn ot appropriate to explain the experimental resultsa nd that the presence of hydrophobic moieties on the alcohol are responsible for the unusual rotational mobility of water. [4][5][6] Anomaloush ydration behavior of alcohols hasb een studied extensively by using variouse xperimental and simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The preferentialh ydration of ap rotein in the presenceo fc osolvents may be regardeda saresult of the delicate balance of three different contributions:arepulsion and an attraction between the protein andc osolventa nd the steric exclusion of the cosolvents acting as classical" crowders". [7][8][9][10][11][12][13][14][15][16][17][18][19] It has been concluded that the conventional "iceberg" modeli sn ot appropriate to explain the experimental resultsa nd that the presence of hydrophobic moieties on the alcohol are responsible for the unusual rotational mobility of water. [4][5][6] Anomaloush ydration behavior of alcohols hasb een studied extensively by using variouse xperimental and simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Anomaloush ydration behavior of alcohols hasb een studied extensively by using variouse xperimental and simulation techniques. [7][8][9][10][11][12][13][14][15][16][17][18][19] It has been concluded that the conventional "iceberg" modeli sn ot appropriate to explain the experimental resultsa nd that the presence of hydrophobic moieties on the alcohol are responsible for the unusual rotational mobility of water. [20] Alcohol/water mixtures are not homogeneous throughout the entire concentration range; [21] the heterogeneity arises due to incomplete mixing as ar esult of cluster formation as well as self-aggregation of the alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Фiзична природа релаксацiйних процесiв водно-спиртових розчинiв обговорюється в [9]. У цьому оглядi на основi аналiзу великої кiлькостi експериментальних фактiв було показано, що спостерiгаються закономiрностi, якi природно пояснюються при залученнi гiпотези про мiкронеоднорiдну будову розчинiв [9][10][11][12]. На це вказують: 1) особливостi розсiяння c ○ Ю.М.…”
Section: вступunclassified
“…Can the sequence of spectroscopic scans under certain fixed conditions and with one varying parameter be used to describe the preconditions of a weak reaction (or, in other words, the creation of a bound state of two molecules, here CO and HF)? The certain type of problems can be solved in the term of chemic ○ A.S. SIZHUK, 2016 cal kinetics (see, e.g., [15]) or by using a new technique [16]. In comparison with the mentioned methods, we will demonstrate the result of Fourier infrared broad band scanning for the mixture with the time-dependent density of carbon monoxide.…”
Section: Introductionmentioning
confidence: 99%
“…I also thank Dr. J. Bevan's group and the Laboratory for Submm/THz Science and Technology at Texas A & M University (College Station, Texas, USA) for providing the support and consultations. + 1 − 6 subband in the hydrogen-bonded system16 O 12 C• • • 1 H 19 F, J. Chem. Phys.…”
mentioning
confidence: 99%